THE INFLUENCE OF THE BANDUNG DISTRICT TOURIST AREA TRANSPORTATION SYSTEM - Agung, Gusti Muhammad; Ismiyati, Ismiyati; Handadjani, Mudjiastuti (Ridwan Institute, 2024)
One of the problems with the transportation system to tourist locations in the Bandung Regency area is congestion which causes an increase in average daily traffic (LHR) due to the use of private vehicles. If the vehicle's LHR increases, the vehicle speed will be low and the cost of transporting the vehicle to tourist locations will become expensive. This research aims to calculate the BOK for the Bandung Regency tourist area, calculate the BOT for the Bandung Regency tourist area and analyze the influence of the transportation system in the Bandung Regency tourist area. The research method uses quantitative and qualitative research (mix method). From the results of BOK calculations and analysis using the Pacific Consultant International (PCI) method, the total BOK value for working days and holidays for Curug Cinulang is IDR 56,582.00. Tebing Keraton Rp. 79,841.00, and Ranca Upas Rp. 103,366.00. From the results of BOT calculations and analysis using the Pacific Consultant International (PCI) method, the total BOT value for weekdays and holidays for Curug Cinulang is IDR 59,714.00. Tebing Keraton Rp. 50,959.00 and Ranca Upas Rp. 108,137.00. Based on the results of the analysis, It can be seen from the indicators that the obstacles faced in daily activities, especially in traveling, are having to deal with traffic jams which cause low vehicle speeds, wasting a lot of time and fuel on the road, thus disrupting travel activity plans.